The availability of Solar illumination at Roorkee (MAUSAM, 1965)
Measurements of the availability of solar illumination on an external horizontal surface at Roorkee are described. The measured values are compared with those calculated from the empirical formula proposed by Elvegard and Sjostedt for clear skies. It is found that the constants of this formula need modification to fit the observations at Roorkee. The illumination corresponding to a cal/sq. cm/min of total radiation incident on the horizontal surface from the sky and sun was also computed from the thermal data available for Roorkee. These computed values agree within 10 per cent of those reported in the literature.